The Dual Nature of Pesantren: Navigating the Power of Religious Leadership in Economic Transformation - Rohmah, Noer; Husniyah, Farihatul; Latif, Adibah Abdul (Institut Agama Islam Negeri Lhokseumawe, 2025)
Pesantren-based community empowerment is an important strategy in facing the challenges of structural poverty and unemployment in the local environment. This study aims to identify the community business empowerment strategy implemented by Kiai Abdullah Syam and evaluate the results of its implementation in the context of economic and social strengthening of the community around the pesantren. The method used is descriptive qualitative with observation techniques, in-depth interviews, and documentation in the pesantren assisted by Kiai Abdullah Syam. Data collection instruments were developed triangulatively to ensure the validity of the findings. The main results show an improvement in the community's quality of life through the establishment of productive economic institutions, strengthening social capital, increasing family income, and integrating religious values in the work ethic. This research is useful in community development, Islamic economics, and pesantren education, and it is relevant for interdisciplinary studies on education management and development sociology. The novelty of this study lies in combining modern marketing strategies with spiritual approaches and pesantren values that have not been widely studied in the empowerment literature. This research contributes to expanding community-based empowerment models that are contextualized and can be replicated in similar communities. In conclusion, pesantren-based empowerment strategies have proven effective in building economic independence and strengthening community social cohesion sustainably